COMPARATIVE ANALYSIS OF THE FINANCIAL PERFORMANCE OF THE GOVERNMENTS OF THE CITY OF BEKASI AND THE CITY OF SURABAYA BEFORE AND AFTER COVID-19 - Bani Zamzami (Asosiasi Dosen Muda Indonesia, 2024)
The aim of this research is to analyze the comparative financial performance of two institutions government in the four main financial years, namely 2019, 2020, 2021 and 2022. This analysis is to understand how the pandemic has impacted several aspects of financial performance, such as income, budget expenditure, deficit, etc. This study uses a descriptive quantitative method by observing a number of financial ratios, including the independence ratio, effectiveness and efficiency ratio, activity ratio and growth ratio. Bekasi City's financial performance is more stable after the pandemic with a maintained surplus and an optimal ratio of independence, effectiveness and shopping activities. While Surabaya is very independent and fantastic in terms of income & expenditure, its spending activity ratio is inferior to Bekasi and experiences large deficits every year. Therefore, this research has an important objective to identify significant changes in the APBD of these two cities before and after the COVID-19 Pandemic, as well as to explore the factors that contributed to these changes, so that they can make a positive contribution in maintaining regional financial stability and supporting efforts for sustainable economic recovery.